2018
DOI: 10.1017/s1355617718000930
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Risk-Aversion After Right DLPFC Stimulation: Effects of rTMS on a Risky Ball Throwing Task

Abstract: Objectives: Several studies on human risk taking and risk aversion have reported the involvement of the dorsolateral prefrontal cortex (DLPFC). Yet, current knowledge of the neural mechanisms of risk-related decision making is not conclusive, mainly relying on studies using non-motor tasks. Here we examine how modulation of DLPFC activity by repetitive transcranial magnetic stimulation (rTMS) affects risk-taking behavior during a motor response task. Methods: One-Hertz rTMS to the right DLPFC was applied to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Perhaps different brain mechanisms are involved in performance on the CGT. Tulviste and Bachmann (2018) found that rTMS to the right DLPFC decreases risk-aversion, so it is possible that the left DLPFC is not actively involved in this pathway. Yang, Khalifa, and Völlm (2018a) found no significant changes regarding impulsivity following excitatory rTMS applied to the right inferior frontal gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps different brain mechanisms are involved in performance on the CGT. Tulviste and Bachmann (2018) found that rTMS to the right DLPFC decreases risk-aversion, so it is possible that the left DLPFC is not actively involved in this pathway. Yang, Khalifa, and Völlm (2018a) found no significant changes regarding impulsivity following excitatory rTMS applied to the right inferior frontal gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…Astonishingly, recent findings have demonstrated that tDCS could have a modulatory effect on decision making and impulsivity in samples of healthy adults and individuals with gambling disorders [ 24 , 25 , 26 , 27 ]. Among different brain target areas, the prefrontal cortex (PFC) and DLPFC have been deemed to play a pivotal role in risky decision making; this conjecture seems to be more conceivable for the right hemisphere of the brain [ 24 , 27 ]. In this regard, Soyata et al [ 26 ] reported that applying 20 min of anodal tDCS over the right DLPFC area improved the decision making and cognitive flexibility of male participants with gambling disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Astonishingly, recent findings have demonstrated that tDCS could have a modulatory effect on decision making and impulsivity in samples of healthy adults and individuals with gambling disorders [24][25][26][27]. Among different brain target areas, the prefrontal cortex (PFC) and DLPFC have been deemed to play a pivotal role in risky decision making; this conjecture seems to be more conceivable for the right hemisphere of the brain [24,27].…”
Section: Introductionmentioning
confidence: 99%
“…TMS evidence suggested that disruption of either the left lateral prefrontal cortex (LPFC) (Figner et al ., 2010) or the right dorsolateral prefrontal cortex (DLPFC) (Knoch et al ., 2006; Tulviste and Bachmann, 2019) increase impulsivity and risk-taking behaviour. Additionally, right anodal/left cathodal dual tDCS on the DLPFC increases response confidence (Minati et al ., 2012), reduces risk-taking behaviour (Fecteau, Knoch, et al ., 2007; Cheng and Lee, 2016), and unpromoted risk-taking strategies that avoid the risk of no reward (Ota et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…TMS evidence suggested that disruption of either the left lateral prefrontal cortex (LPFC) (Figner et al, 2010) or the right dorsolateral prefrontal cortex (DLPFC) (Knoch et al, 2006;Tulviste and Bachmann, 2019) increase impulsivity and risk-taking behaviour.…”
Section: Introductionmentioning
confidence: 99%